2015
DOI: 10.1021/acs.macromol.5b01931
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanoparticle Localization in the Perforated Lamellar Phase of Self-Assembled Block Copolymer Driven by Entropy Minimization

Abstract: Although precisely controlled microdomains of block copolymers (BCP) provide an excellent guiding matrix for multiple nanoparticles (NPs) to be controllably segregated into a desired polymer block, localization and positioning of individual NPs have not been demonstrated. Here, we report a unique one-to-one positioning phenomenon of guest Au NPs in the host BCP microdomains; each of polystyrene-functionalized Au NPs is embedded within the perforation domain of hexagonally perforated lamellar (HPL) morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…, DNA, functionalized polymers, and diblock copolymers) to direct the ordering and local environment of NPs is ideal for scalable fabrication of regular arrays of NPs. Among these, diblock copolymers can spontaneously assemble into a diversity of periodically well-defined nanostructures such as hexagonally close-packed cylinders and lamellae, which are used as scaffolds to host NPs within thermodynamically compatible nanodomains. Such coassembly of diblock copolymer/NP mixtures offers a viable route to prepare hybrid materials integrating unique functionalities of fillers and matrices. However, because of the impractically slow self-assembly kinetics and long-lived defects in the ordering process, the diblock copolymers self-assemble into poorly ordered nanostructures, whose grain sizes have several disparate periodicities. These phenomena result in a grand challenge for efficient manufacturing of regularly defect-free arrays of NPs via the coassembly strategy of diblock copolymer/NP mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…, DNA, functionalized polymers, and diblock copolymers) to direct the ordering and local environment of NPs is ideal for scalable fabrication of regular arrays of NPs. Among these, diblock copolymers can spontaneously assemble into a diversity of periodically well-defined nanostructures such as hexagonally close-packed cylinders and lamellae, which are used as scaffolds to host NPs within thermodynamically compatible nanodomains. Such coassembly of diblock copolymer/NP mixtures offers a viable route to prepare hybrid materials integrating unique functionalities of fillers and matrices. However, because of the impractically slow self-assembly kinetics and long-lived defects in the ordering process, the diblock copolymers self-assemble into poorly ordered nanostructures, whose grain sizes have several disparate periodicities. These phenomena result in a grand challenge for efficient manufacturing of regularly defect-free arrays of NPs via the coassembly strategy of diblock copolymer/NP mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the structures obtained were reproducible across different compositions. Hence, it is possible that the PL morphology observed in the PS-b-P4VP/CdSe−CdS composites is an equilibrium morphology very similar to that observed by Nam et al 15 in the case of thin films of PDMS-b-PS/AuNP composites. It was shown that the perforated regions in the PL morphology of thin films of PDMS-b-PS/AuNPs mixtures can precisely host single AuNP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Even if in the bulk state, the perforated lamellar morphology of block copolymers has been reported to be a metastable state of the gyroid (G) phase, under thin film confinement conditions, one-dimensional confinement provides stability to the phase [26,27] and has been found for different diblock copolymer thin films under several conditions [26][27][28][29][30][31][32][33][34][35]. For thin films of poly(styrene-b-dimethylsiloxane) (PS-b-PDMS) diblock copolymer spin coated onto silicon wafers modified with hydroxyl-terminated PDMS subject to solvent vapor annealing, depending on the film thickness, its commensurability with the microdomain period, and the ratio of toluene/heptane vapors used for the solvent annealing process, perforated lamellae morphology can be obtained [26], besides spheres, cylinders, or gyroids.…”
Section: Perforated Lamellar Morphologymentioning
confidence: 99%